2007
DOI: 10.1007/s11258-007-9358-x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal by cattle of salt-marsh and dune species into salt-marsh and dune communities

Abstract: Seed dispersal via ingestion and defecation by large herbivores (endozoochory) plays a potentially important role in structuring plant communities. In the present study we tested whether cattle disperse seeds between different plant communities in a heterogeneous coastal habitat. We surveyed the seed contents of cattle dung collected from two habitat types within a grazing system, one in dunes and the other in saltmarsh. The dunes are characterized by sandy soil, and infrequent inundation by the sea, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Similar results have also been found in other grazing systems (Bakker et al. ; Stroh et al. in press).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have also been found in other grazing systems (Bakker et al. ; Stroh et al. in press).…”
Section: Discussionsupporting
confidence: 90%
“…They can travel rapidly – thereby bringing about long‐distance seed dispersal (i.e. > 100 m; Cain et al , Heinken et al , Mouissie et al ) – and they use a wide variety of habitats (Nugent , Heinken et al , Bakker et al , Kuiters and Huiskes ).…”
Section: Description Of the Different Plant And Ungulate Traits Knownmentioning
confidence: 99%
“…It is highest in the dunesaltmarsh transition probably due to the higher abundance of palatable species (Bakker et al 2008), which could be shown by the higher forage value. Moreover, the data show a trend that rabbits probably prefer light and moderately warm sites for grazing.…”
Section: Habitat Preferencementioning
confidence: 98%